2020
DOI: 10.3389/fnins.2020.525144
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Promoted Nerve Repair After Peripheral Nerve Injury by Regulating miR-1b and Its Target Brain-Derived Neurotrophic Factor

Abstract: Growing evidence indicates that electroacupuncture (EA) has a definite effect on the treatment of peripheral nerve injury (PNI), but its mechanism is not completely clear. MicroRNAs (miRNAs) are involved in the regulation of a variety of biological processes, and EA may enhance PNI repair by regulating miRNAs. In this study, the rat sciatic nerve injury model was treated with EA for 4 weeks. Acupoints Huantiao (GB30) and Zusanli (ST36) were stimulated by EA 20 min once a day, 6 days a week for 4 weeks. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…When Schwann cells exposure promoted directed migration, it travels towards the cathode at a mean rate of 7.5 µm/h (Bunn et al, 2019). EA may promote enhanced sciatic nerve function recovery and SC proliferation by down-regulating miR-1b (Liu et al, 2020). At present, there is no de nitive agreement on which of these regimens is more effective.…”
Section: Results Of Nite Element Model 11 the Location Of The Needlesmentioning
confidence: 99%
“…When Schwann cells exposure promoted directed migration, it travels towards the cathode at a mean rate of 7.5 µm/h (Bunn et al, 2019). EA may promote enhanced sciatic nerve function recovery and SC proliferation by down-regulating miR-1b (Liu et al, 2020). At present, there is no de nitive agreement on which of these regimens is more effective.…”
Section: Results Of Nite Element Model 11 the Location Of The Needlesmentioning
confidence: 99%
“…For nerve conduction velocity recovery rate (NCV), the NCV of the bilateral sciatic nerve was assessed, as previously described [ 15 ]. In brief, the stimulating electrode and the receiving electrode were connected to the proximal and distal ends of the sciatic nerve, respectively, using the copper handle of the acupuncture needle.…”
Section: Methodsmentioning
confidence: 99%
“…Electroacupuncture (EA) is defined as a combination of electrical stimulation with acupuncture needles and is capable of promoting the regeneration of the transected median nerve in rats [ 13 ] and increasing neuronal stem cell growth [ 14 ]. We have confirmed that EA could promote Schwann cells (SC) proliferation and the release of neurotrophic factors (NTFs), including brain-derived neurotrophic factor (BDNF) [ 15 ] and nerve growth factor (NGF) [ 16 ] after PNI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro , it was confirmed that the overexpression of mir-1b could inhibit the expression of brain-derived neurotrophic factor (BDNF) in the rat Schwann cell line. The research may indicate that the electroacupuncture might promote Schwann cell proliferation and recovery of sciatic nerve function by downregulating mir-1b ( 26 ).…”
Section: Recovery Of Function After Traumamentioning
confidence: 99%